Medium optimization for high mycelial soluble protein content of Ophiocordyceps sinensis using response surface methodology - Tang, Chu-Yu; Wang, Jie; Liu, Xin; Chen, Jian-Bo; Liang, Jing; Wang, Tao; Simpson, Wayne Roydon; Li, Yu-Ling; Li, Xiu-Zhang (Frontiers in Microbiology, 2022)
Ophiocordyceps sinensis is widely utilized due to its pharmaceutical value. Mycelial protein forms a key active component of O. sinensis and determines the medicinal potential of fungus. Here, we describe the development of an optimized fermentation medium to obtain more mycelial soluble protein from O. sinensis using response surface methodology (RSM) and investigate the increased mycelial protein content using transcriptomics. The maximum mycelial protein content of 2.11% was obtained using a medium consisting of 20% beef broth, 0.10% peptone, 2% glucose, 0.15% yeast extract, 0.20% KH2PO4, and 0.02% MgSO4. Transcriptome analysis identified 790 differentially expressed genes (DEGs), including 592 up-regulated genes and 198 down-regulated genes, optimisation resulted in more up-regulated genes. The main DEGs were enriched in metabolic pathways, ABC transporters, starch and sucrose metabolism, tyrosine metabolism, and glutathione metabolism. In addition, some DEGs associated with mycelial protein enhancement such as tyrosinase (TYR), glutathione S-transferase (GST), glutamine synthetase (glnA), and β-glucosidase may contribute to increased mycelial protein content. Real-time Quantitative PCR (RT-qPCR) was used to confirm gene expression and the results support the accuracy of RNA-Seq and DEG analysis. This study provides an optimized fermentation method for enhancing the mycelial protein content of O. sinensis and a reference for the effective development of O. sinensis protein.